Evolutionary game and simulation analysis on management synergy in China’s coal emergency coordination - Shi, Peizhe; Hao, Yu; Sun, Chaolun; Zhang, LiJun (Frontiers in Environmental Science, 2023)
Once coal mine accidents occur, a series of chain reactions will bring radiation effects that are difficult to solve in the short term to the normal operation of the economy and society. Therefore, the post-disaster management of coal mine accident is particularly important. Coal mine emergency response involves many stakeholders, and it needs various regions, departments to achieve multi-agent, multi-level effective collaboration to ensure that the coal mine accidents are controlled as soon as possible. Local governments and coal mine enterprises are the main forces in the post-accident emergency management of coal mines, but the differences in their interest motives, preferences and cognitive structures make it difficult for the relevant emergency managers to make correct decisions in the complex accident management environment, therefore, the game relationship between conflict and cooperation among related subjects is explored based on the perspective of game theory. This study establishes a game model of coal mine accident response behavior between coal mining enterprises and local governments, and quantitatively adopts the method of numerical simulation analysis to conduct in-depth analysis of the influencing factors of their decision-making behavior. The results reveal that: 1) the establishment of an information sharing mechanism is an important condition for local governments to efficiently and quickly start the incident response process for coal mine accidents; 2) Under the proper supervision of local government, the impact of the reduction of emergency response cost on the active response of coal mining enterprises is more significant and direct, that is, The cost of emergency response is the decisive factor affecting the incident response work of coal mining company; 3) the establishment of emergency cost compensation mechanism and incentive mechanism should also be the focus of local governments in formulating emergency coordination policies in the future. This study provides scientifc and reasonable management suggestions in line with the actual situation of China and provides a useful reference for local government to formulate the optimal strategy for emergency coordination in coal mine emergencies, to improve the motivation of each coordinating subjects and to improve the current situation of emergency coordination in China’s coal mines.